Huey P. Newton : the radical theorist - Jeffries, J. L. (Judson L.), 1965- (University Press of Mississippi, 2002)
"Huey P. Newton's powerful legacy to the Black Power Movement and the civil rights struggle has long been obscured. Conservatives harp at Newton's drug use and at the circumstances of his death in a crack-related shooting. Liberals romanticize his black revolutionary rhetoric and idealize his message. In Huey P. Newton: The Radical Theorist, Judson L. Jeffries considers the entire arc of Newton's political role and influence on civil rights history and African American thought. Jeffries argues that, contrary to popular belief, Newton was one of the most important political thinkers in the struggle for civil rights"--Jacket